2023
DOI: 10.3390/magnetochemistry9070170
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Magnetocaloric Properties of Nano- and Polycrystalline Bulk Manganites La0.7Ba(0.3−x)CaxMnO3 (x ≤ 0.25)

Roman Atanasov,
Ecaterina Brinza,
Rares Bortnic
et al.

Abstract: Here we report the synthesis and investigation of bulk and nano-sized La0.7Ba0.3−xCaxMnO3 (x = 0, 0.15, 0.2 and 0.25) compounds that are promising candidates for magnetic refrigeration applications. We compare the structural and magnetic properties of bulk and nano-scale polycrystalline La0.7Ba0.3−xCaxMnO3 for potential use in magnetic cooling systems. Solid-state reactions were implemented for bulk materials, while the sol–gel method was used for nano-sized particles. Structurally and morphologically, the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…142 For instance, substitution at the A-site includes La 0.7 Ca 0.3 MnO 3 , 117 and La 0.7 Ba 0.05 Ca 0.25 MnO 3 . 77 which exhibit higher −Δ S M values than LaMnO 3 . Based on several studies, it can be concluded that A-site substitution with low-valence ions significantly influences changes in magnetic entropy and T C , often exhibiting extreme values that need to be considered for the effects of substitution in Mn 3+ /Mn 4+ in the material system.…”
Section: Phenomena and Parameters Influencing The Behavior Of Mce In ...mentioning
confidence: 94%
See 2 more Smart Citations
“…142 For instance, substitution at the A-site includes La 0.7 Ca 0.3 MnO 3 , 117 and La 0.7 Ba 0.05 Ca 0.25 MnO 3 . 77 which exhibit higher −Δ S M values than LaMnO 3 . Based on several studies, it can be concluded that A-site substitution with low-valence ions significantly influences changes in magnetic entropy and T C , often exhibiting extreme values that need to be considered for the effects of substitution in Mn 3+ /Mn 4+ in the material system.…”
Section: Phenomena and Parameters Influencing The Behavior Of Mce In ...mentioning
confidence: 94%
“…Generally, size reduction strategies from micro to nanoscale in MCE materials can affect the broadening of the magnetic phase transition, resulting in a broader working temperature range, a decrease in saturation magnetization, and −Δ S M value. 51,65,77–80 These changes are associated with disturbances such as strain fields, atomic disorder, uncompensated surface spins, chemical inhomogeneity, grain size distribution, etc. 65 For example, Zeng et al reduced the size of Gd material to as small as 15 nm, resulting in a reported decrease in the −Δ S M value by up to 50% compared with micro-sized samples.…”
Section: Challenges and Various Types Of Mce Materials For Future App...mentioning
confidence: 99%
See 1 more Smart Citation